2017
DOI: 10.1038/s41467-017-01066-6
|View full text |Cite|
|
Sign up to set email alerts
|

Signatures of the topological s +− superconducting order parameter in the type-II Weyl semimetal T d-MoTe2

Abstract: In its orthorhombic T d polymorph, MoTe2 is a type-II Weyl semimetal, where the Weyl fermions emerge at the boundary between electron and hole pockets. Non-saturating magnetoresistance and superconductivity were also observed in T d-MoTe2. Understanding the superconductivity in T d-MoTe2, which was proposed to be topologically non-trivial, is of eminent interest. Here, we report high-pressure muon-spin rotation experiments probing the temperature-dependent magnetic penetration depth in T d-MoTe2. A substantial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
132
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(157 citation statements)
references
References 71 publications
23
132
0
Order By: Relevance
“…A high-pressure muon-spin rotation study of superconductivity in MoTe 2 suggested that a topologically non-trivial s +− state likely exists in MoTe 2 at pressures up to 1.9 GPa. 18 Key components to a TSC state are the crystal structure and band topology under pressure. Existing reports stop short of exploring the symmetry in the superconducting phase under pressure and no calculations exist on the electronic band structure.…”
Section: Introductionmentioning
confidence: 99%
“…A high-pressure muon-spin rotation study of superconductivity in MoTe 2 suggested that a topologically non-trivial s +− state likely exists in MoTe 2 at pressures up to 1.9 GPa. 18 Key components to a TSC state are the crystal structure and band topology under pressure. Existing reports stop short of exploring the symmetry in the superconducting phase under pressure and no calculations exist on the electronic band structure.…”
Section: Introductionmentioning
confidence: 99%
“…MoTe 2 is an interesting member of the family of the transition metal dichalcogenides because of the multiple structural phases in which the compound can exist. 25,26 At 250 K, MoTe 2 shows a structural phase transition where a high temperature inversion symmetric monoclinic phase finds a new ground state with noncentrosymmetric orthorhombic structure (space group: P mn21, T d Phase). 27 The Orthorhombic T d phase is a Weyl semimetal 28,29 which is also known to show superconductivity below a very low critical temperature (T c ) of 0.1 K. 30 By introducing strain in the crystals of MoTe 2 through large external hydrostatic pressure, it has also been possible to enhance the T c of MoTe 2 significantly.…”
mentioning
confidence: 99%
“…The data of Cu 0.09 Bi 2 Se 3 were extracted from our magnetization measurement, and other data points of Cu x Bi 2 Se 3 were obtained from magnetization and μSR measurements in previous reports [53,55]. [143], Nb 0.5 Os 0.5 [114], Re 6 Zr [144], Mo 3 P [113], and BeAu [145], thin films of transition-metal nitrides NbN [14,91], heavy fermions superconductors UPt 2 , UBe 13 and Ce 1−x Yb x CoIn 5 [146][147][148], and conventional metal superconductors [82,119].…”
Section: Discussionmentioning
confidence: 98%